Optimizing the admission time of outbound trucks entering a cross-dock with uniform arrival time by considering a queuing model. Issue 3 (4th March 2017) - Motaghedi-Larijani, Arash; Aminnayeri, Majid
ABSTRACT: Cross-docking is a supply-chain strategy that can reduce transportation and inventory costs. This study is motivated by a fruit and vegetable distribution centre in Tehran, which has cross-docks and a limited time to admit outbound trucks. In this article, outbound trucks are assumed to arrive at the cross-dock with a single outbound door with a uniform distribution (0, L ). The total number of assigned trucks is constant and the loading time is fixed. A queuing model is modified for this situation and the expected waiting time of each customer is calculated. Then, a curve for the waiting time is calculated. Finally, the length of window time L is optimized to minimize the total cost, which includes the waiting time of the trucks and the admission cost of the cross-dock. Some illustrative examples of cross-docking are presented and solved using the proposed method.